THE RESPONSIBILITY OF PROTECTING (R2P) HUMAN RIGHTS AND SECURITY COUNCIL - ULDARICIO FIGUEROA PLÁ (Política y Estrategia, 2017)
The adoption in 1948 of the Convention on the Prevention and Punishment of the Crime of Genocide seemed to open a new era in the international scenario in which these kind of practices apparently are left in the historic past. Reality has shown us that this international instrument was not enough to face arbitrary measures of some Governments. Nevertheless, genocide actions continuing to be performed, and in order to decrease human suffering, “humanitarian intervention” was thought as a response to the ineffectiveness of the Security Council which also brought along arbitrary actions in its invocation, discrediting it. Before the reiterated calls of the Secretary General of the United Nations to prevent and detain massive violations to human rights, an effort has been made in order to standardizing a type of interventions that can respond to massive violations of human rights. This has been called Responsibility to Protect.